The Analysis of Understanding Level of 2nd Grade Student Concerning Japanese Particle Wo (International Journal of Psychosocial Rehabilitation, 2020)
Human use language when they do interaction and communicate in the society. Good communication needs good linguistics knowledge. Therefore, it is necessary to make a sentence with good capability of understanding the vocabularies and know how to choose the correct ones. To make a good sentence in a communication, beside those two important factors mentioned above, it is also necessary to be able to make a correct structure of a sentence. In Japanese language, one thing that is very important that we should have is the good knowledge of joshi (particles), especially to make a writing. However, sometimes as there are many joshi used in a sentence, it is very difficult and confusing for Japanese learners to decide which one that is appropriate to be used. This research studies joshi (particle) wo as the research object, and furthermore will divine the using of particle wo in a sentence that has many functions, depend on its following verbs. After conducting the research, it is known that the understanding level of the 2nd grade of students of Japanese Department in Widyatama University towards the function of particle wo is quite high, however it depends on the following verbs. This research is using descriptive method by quantitative approach, and conducted by test as its instrument and also questionnaires. This study’s objective is the 2nd grade of students of Japanese Department in Widyatama University.